EVALUAREA INIŢIALĂ - SUPORT PENTRU FORMAREA COMPETENŢELOR LICEENILOR LA CHIMIE - USM ADMIN (Moldova State University, 2008)
This article discusses the topic of initial assessment as a support for development of student's disciplinary compe- tences on chemistry. Competence involves integrated complexes of knowledge, abilities, and capacities. Accurate and effective initial assessment is necessary for identifying students' level of knowledge and skills, while having the goal to assure the premises for realization of the curricular objectives in the lyceum.